Malignant Conversion of a Solitary Papilloma in the Distal Trachea: Report of a Case - Achilleas Lioulias; Panagiotis Misthos; Georgios Papagiannakis; Dimitrios Mermigkis; Napoleon Karagianidis; Kostas Neofotistos; John Kokotsakis (Canadian Respiratory Journal)
A solitary papilloma versus the usual multiple lesions of papillomatosis is extremely rare. Even more infrequent is a solitary papilloma of the trachea in an adult patient. In the present report, a case of a solitary papilloma in the distal trachea is presented. After two unsuccessful sessions of laser ablation, resection of the lower one-third of the trachea was performed through a right posterolateral thoracotomy. Postoperative histology results disclosed a malignant degeneration into squamous cell carcinoma. The patient had an excellent outcome after resection of the affected portion of the trachea. There was no evidence of recurrence after 20 months of follow-up.